Analisis Faktor-Faktor yang berhubungan dengan Kepatuhan Perawat dalam Penerapan Identifikasi Pasien diruang Rawat Inap Penyakit Dalam RSUP dr. M. Djamil Padang - Eliwarti Eliwarti (Jurnal Akademika Baiturrahim Jambi, 2021)
The patient of rescue incident is an accidental event and condition which give impact or have potential injury that can be prevented by patient. The mistake of misunderstanding often happened to the most all aspects or stages diagnoses and healing, so that it is needed patient identification properly. The aim of this research is to know the factors which related to the adherence of nurses in applying patients identification of internest department in inpatient room Dr. M. Djamil hospital Padang. This research is descriptive corelation study with collecting the data as cross sectional. The sample were 66 nurses with proportion sampling random. The data analysis with chi-square test. The result of the research showed that nurses perceived high motivation (50%), complete facilities (74.2%), good supervision (57.6%), high social support (54.5%), high knowleage (90.9%). Adherence nurses (63.6%). There significant relationship between facilities factors and supervision with adherence nurses in applying of patients identification . There was no significant relationship between  motivation factors, knowleage, social support with adherence nurses in applying of patients identification. The facilities of dominant variable in assembling patient identification (OR 19.789). It is recommended that hospital to do supervision as continiue and collect the facilities patient identification to perform patients identification properly and give punishment to the nurses properly who do not perform patients identification corectly.